Development of FPGA-based standalone, portable TDCR system - Sharma, M.K.; Agarwal, Shivam; Kulkarni, M.S.; Baraiya, S.V.; Kulkarni, D.B. (Journal of instrumentation, 2023)
A standalone, lightweight, portable, FPGA-based triple to double coincidence ratio (TDCR) system is developed. The optical chamber of the system is fabricated in a dual, coaxial cylindrical geometry, with the inner cylinder made up of Teflon and the outer one of aluminium. Three square PMTs, each having an active cathode area of 2.3 cm × 2.3 cm, are housed in the optical chamber. The variation in detection efficiency to identify the optimum kB (ionization quenching parameter) value is achieved by changing the vial position vertically with respect to the centre line of the PMTs. The coincidence analyzer implemented in a field programmable gate array (FPGA) transfers the pulse counts and associated parameters in real time to a Raspberry Pi single board computer (SBC). The TDCR algorithm to compute the efficiency is implemented in the SBC. In addition, the SBC is interfaced with a local 7” touchscreen to provide an intuitive graphical user interface (GUI) for operating the standalone instrument. The system performance is validated with 3 H and 14 C radionuclide standards.